2022
DOI: 10.1186/s12885-022-09970-x
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a-5p regulates proliferation, apoptosis, migration and invasion via inhibiting hydroxysteroid dehydrogenase like-2 in cervical cancer cell

Abstract: Background Evidences have indicated that miR-26a-5p regulates the malignant properties of various tumor cells. However, the influences of miR-26a-5p on proliferation, apoptosis and invasion are still vague in the cervical cancer (CC) cells. Methods The miRNA microarray and real-time quantitative PCR (RT-qPCR) analysis were utilized to detect the expression of miR-26a-5p in the patients with CC. Kaplan–Meier plotter was performed to evaluate the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In previous studies, miR‐26a‐5p has shown a promising biological effects and therapeutic potential in various diseases. Many investigations reported the anticancer effect of miR‐26a‐5p through inducing apoptosis, inhibiting proliferation, and decreasing metastasis of different cancer cells 53–55 . Apart from cancers, miR‐26a‐5p also exhibit protection in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, miR‐26a‐5p has shown a promising biological effects and therapeutic potential in various diseases. Many investigations reported the anticancer effect of miR‐26a‐5p through inducing apoptosis, inhibiting proliferation, and decreasing metastasis of different cancer cells 53–55 . Apart from cancers, miR‐26a‐5p also exhibit protection in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations reported the anticancer effect of miR‐26a‐5p through inducing apoptosis, inhibiting proliferation, and decreasing metastasis of different cancer cells. 53 , 54 , 55 Apart from cancers, miR‐26a‐5p also exhibit protection in cardiovascular diseases. It could protect against myocardial ischemia/reperfusion injury by regulating PTEN/PI3K/AKT signaling pathway 56 and also alleviates myocardial infarction by regulating ATG12‐mediated autophagy in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dong et al demonstrated that miR-26a-5p is a tumor suppressor that inhibits cell proliferation and invasion of cervical cancer cells under physiological conditions by targeting protein tyrosine phosphatase type IVA1 (49). In contrast, Li et al, 2022 identified a different target (50). They demonstrated a negative correlation of miR-26a-5p with hydroxysteroid dehydrogenases like 2 and described a therapeutic potential in increasing miR-26a-5p expression.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1297 and miR-26a-5p are other miRNAs that have been studied in cholesteatoma and are widely investigated in oncology. The inhibitory effect of miR-1297 on cancer progression has been observed in various malignant entities [113][114][115][116][117][118][119][120][121][122][123][124]. In addition to its role in tumorigenesis, miR-26a-5p similarly plays an important role in pulmonary fibrosis [125] and Alzheimer's disease [126].…”
Section: Microrna-802mentioning
confidence: 99%